INVESTIGATION OF USAGE IN DYEING OF TEXTILE OF POMEGRANATE (PUNICA GRANATUM) JUICE - Huseyin Efil; Adem Önal; Ferda Eser; Uğur Çakır (Journal of New Theory)
In this study, the dyeing properties of pomegranate (Punica granutum) juice were investigated. Its juice was obtained by extraction (cool press) to obtain the dyebath. Aluminium sulphate Al(SO4)3, Iron (II) sulphate (FeSO4), Copper (II) sulphate (CuSO4)salts and ( NH3 + calcium oxalate + urea) solution 3% g/v) were used as mordants for mordanting of wool, viscose and linen fabrics. All fabrics were dyed at different pH values (4 and 7) using together mordanting, pre-mordanting and last mordanting methods). Consequently, 11 wool, 11 viscose and 11 linen fabric samples were dyed at two different pH degree (4 and 7). Color codes, fastness measurements and dyeing conditions were determined